2016
DOI: 10.3233/bsi-160157
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of cholesterol in cellular biomechanics and regulation of vesicular trafficking: The power of imaging

Abstract: Abstract.Cholesterol is an important component of cell plasma membrane. Due to its chemical composition (long rigid hydrophobic chain and a small polar hydroxyl group), it fits most of its structure into the lipid bilayer, where its steroid rings are in close proximity and attracted to the hydrocarbon chains of neighboring lipids. This gives a condensing effect on the packing of lipids in cell membranes creating cholesterol-enriched regions called membrane rafts, which also congregate a lot of specific protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 115 publications
2
12
0
Order By: Relevance
“…The different distribution of cholesterol and phospholipids seems not to be crucial for either the overall mechanical properties of the cell or their spatial distribution. These results, although not intuitive, are in agreement with literature data when the stiffening of cells is observed for cholesterol depletion [ 73 , 74 , 75 ].…”
Section: Discussionsupporting
confidence: 92%
“…The different distribution of cholesterol and phospholipids seems not to be crucial for either the overall mechanical properties of the cell or their spatial distribution. These results, although not intuitive, are in agreement with literature data when the stiffening of cells is observed for cholesterol depletion [ 73 , 74 , 75 ].…”
Section: Discussionsupporting
confidence: 92%
“…These include cholesterol-binding agents such as filipin and perfringolysin O, chemically related steroids such as dehydroergosterol, which are intrinsically fluorescent, and fluorescently labeled cholesterol derivatives, mostly either modified at the C3-position (3-NBD-Cholesterol), at the double bond (6-Dansyl-Cholestanol), or at the terminus of the alkyl backbone (TopFluor/BODIPY-cholesterol). However, the dynamic visualization of cholesterol distribution in live cells using these markers has proven to be difficult, e.g., due to poor delivery of the labeled derivatives into cells, the prerequisite for cell fixation, relatively weak staining and resolution, or perturbation of the native membrane organization because of less efficient packing 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in addition to their potential as lipid-lowering agents, as well as the cellular intake and efflux. The cholesterol level in cells appears to affect the activity of numerous membrane-associated proteins and the intensity of various cellular processes [17][18][19] with the sterolregulatory element-binding protein (SREBP) as the key regulator of cholesterol biosynthesis. Several potential mechanisms [20] have been proposed by which cholesterol may affect cell functioning, as will be briefly highlighted below.…”
Section: Extending the Potential Of Sqsis To Therapeutic Areas Othementioning
confidence: 99%
“…Frisz et al [28] visualized sphingolipid domains in the plasma membranes of fibroblasts using high-resolution imaging mass spectrometry of Multiple recent studies point toward the involvement of the actin cytoskeleton in shaping the cell membrane organization, and in many cases, cholesterol was shown to interfere with the actindependent membrane structuring. [19,29] For example, the segregation of the gangliosides GM1 and GM3 depends on the actin cytoskeleton, and cholesterol depletion reduced their clustering. [30] Kwik et al [31] concluded that cholesterol depletion reduced the lateral mobility of membrane proteins because it disrupted the highly regulated interactions of the regulatory phospholipid phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ) with molecules controlling the state and organization of the actin cytoskeleton.…”
Section: Cholesterol and The Actin Cytoskeletonmentioning
confidence: 99%